Ayat Al-Qur'an dan Hadis Tentang Pemimpin Ideal dalam Manajemen Pendidikan Islam - Yovica, Alia; Bustamam, Risman; Oktavia, Lidya Fransiska (Indo-MathEdu Intellectuals Journal, 2025)
Leadership in Islam has a broad dimension, encompassing the values of trust, responsibility, and accountability before Allah SWT. In the context of Islamic education, a leader not only plays the role of managing educational institutions but also serves as a moral and spiritual example for students and educators. This article aims to examine the concept of the ideal leader from the perspective of the Qur'an, Hadith, and the views of Islamic education experts. Leaders in Islam are identified through concepts such as caliph, imam, uswah, qudwah, and qawwam, which emphasize the importance of fair, wise, and responsible leadership. This study employs a literature study method (library research) by analyzing various primary and secondary sources, such as the interpretation books, collections of hadith, and academic literature related to leadership in Islamic education. This article also includes an analysis of relevant hadiths and case studies on the implementation of ideal leadership in the context of Islamic education. The findings indicate that leadership in Islamic education must be based on the principles of honesty, justice, responsibility, and exemplary action